Citocompatibilidade, propriedades antibiofilme e físicas e cimentos endodônticos associados à amoxilina - Andolfatto, Carolina [UNESP] (2015)
Sealers associatedwith amoxicillinhave been developed as an alternative to root canal filling. The objectives of this study were to evaluate the cytocompatibility of AH Plus and Sealapex associated with amoxicillin in concentration of 10% of the total weight of sealer (Chapter 1) and evaluate the flow and the setting time of AH Plus sealer and Sealapex associated with amoxicillin at different concentrations and the activity of sealers antibiofilm associated with higher concentrations of amoxicillin which does not alter the physical properties of both sealers (Chapter 2). In Chapter 1 cytocompatibility of the materials was assessed using the L929 fibroblasts exposed for 24 hours with different dilutions of the extracts of pure sealer and associated with amoxicillin. The testing of 3- (4,5-dimethyl-2-thiazolyl) -2,5-diphenyl-2H-tetrazolium (MTT), and neutral red were used for evaluation of cell viability and fluorescence actin and α-tubulin were used for analysis of the cytoskeleton. Data were analyzed using analysis of variance and two criteria Bonferroni post test at 5% significance level. The results showed that incorporation of amoxicillin at a concentration of 10% by weight of the sealer did not decrease the viability of fibroblasts and did not cause structural changes in the cytoskeletal components studied. It is concluded that amoxicillin could be a promising antimicrobial agent to be incorporated in sealers. In chapter 2 the flow and setting time of the sealer pure or associated with amoxicillin from 0.25 to 10% concentrations were evaluated according to no 6876 specification of the International Organization for Standardization (ISO 2012). The antibiofilm evaluation of pure sealer and 1% associated with amoxicillin was performed by direct contact test with Enterococcus faecalis biofilm previously induced in bovine dentin for 14 days. Fresh sealer were in contact with the biofilm... (Complete abstract electronic access below)